MODELING OF TRANSPORT SERVICE OF INDUSTRIAL ENTERPRISES WITH LIMITED VEHICLE FLOW - Krasulin, Oleksandr; Khara, Maryna; Doroshenko, Illia; Avramenko, Tamara (European Science, 2024)
At the present stage, an important issue of industrial enterprises in Ukraine is resource and energy saving. In particular, the importance of this issue is quite high for enterprises whose transportation process is based on the use of a railway mode of tr